Fresno County Bar Association Law Day Luncheon: Judge Robert Coyle Speaker - Watkins, Howard::::::::: (1986)
Federal District Court Judge Robert Coyle giving Law Day address at lectern; seated: Lee Cabibi, Thomas Richey and Catherine Golden-Taylor